Design of the conceptual implementation of an apparatus with the induced heat and mass transfer for vaporization and rectification - Pogozhikh, Nikolay; Pak, Andrey O.; Pak, Alina V.; Goralchuk, Andrii; Sabadash, Sergei; Chekanov, Nikolay (Eastern-European Journal of Enterprise Technologies, 2019)
The need to find solutions to problems on the efficient use of energy resources has been substantiated, under conditions for meeting the requirements to the environmental sustainability of production in the process of executing such technological operations as vaporization and rectification. We have identified the prospects of searching for and applying the induced processes, which are characterized by high energy efficiency and are environmentally friendly. The kinetics of temperature have been investigated under the effect from the induced heat transfer of the components of the internal thermostat volume, under condition of using different liquids in its internal environment. Our study has established the impossibility for the liquid in the inner volume thermostat to achieve the boiling temperature under condition of the effect of the induced heat and mass transfer, proven by the visual observations and by the value of its temperature. In the experiment under atmospheric pressure, the thermostat temperature was equal to 115...116 °C, while the temperature of the volumetric water did not exceed 97 °C. It was established that at the thermostat temperature of 105...106 °C and under atmospheric pressure, the ethyl alcohol temperature did not exceed 72...73 °C, and for water ‒ 83...85 °C, under the condition of the effect of the induced heat-and-mass transfer. It was found that ethyl alcohol and water are transferred to the gas state under the effect of the induced heat-and-mass transfer separately. It is possible to register the removal of the liquid phase of the mixture components based on the jump-like transition in the kinetics of the fluid temperature. It was established that the liquid phase did not boil for a mixture of ethyl alcohol with water under the effect of the induced heat-and-mass transfer at the thermostat temperature of 105 °C and under atmospheric pressure. We have proposed a conceptual solution to the technical implementation of the universal device that employs the effect of the induced heat-and-mass transfer in order to execute technological operations of vaporization and rectification excluding the boiling phase. Based on a given conceptual solution, we have built a laboratory prototype of the installation, in which vaporization is carried out under atmospheric pressure at the liquid phase temperature of 83...85 °C. The economic effect from the installation is achieved through the simplified equipment and reduction in energy consumption per product unit by larger than 1.3 times compared to the vacuum-evaporator apparatus